Factors Influencing Personal Hygiene During Menstrual Period Among Adolescent Girls - Musfiroh, Sri (Ann Publisher, 2025)
Background. In West Java, 83% of adolescents lack understanding of reproductive health, and 74% feel insufficient family support during menstruation. Around 70% of genital hygiene problems are caused by the use of inappropriate sanitary pads, compounded by poor practices such as infrequent pad changes or incorrect cleaning techniques. Consequently, adolescents are at risk of experiencing leucorrhea, irritation, and vaginitis. Objective. To examine the factors influencing personal hygiene among adolescent girls during menstruation at SMPN 7 Cirebon City in 2025. Methods. An analytical survey approach was used to explore how and why health-related phenomena concerning menstrual personal hygiene occur. The study employed a cross-sectional design, which observes correlations between risk factors and effects through data collection at a single point in time using an observational approach. Conclusion. Logistic regression analysis showed that knowledge was the most influential factor affecting personal hygiene (p=0.045, OR=0.70). Adolescents with good knowledge were 0.70 times more likely to practice proper personal hygiene compared to those with poor knowledge.Implementation. It is necessary to improve adolescents’ knowledge about personal hygiene through school-based learning.